2011
DOI: 10.1074/jbc.m110.180661
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A-α Directly Phosphorylates FoxO1 in Vascular Endothelial Cells to Regulate Expression of Vascular Cellular Adhesion Molecule-1 mRNA

Abstract: Forkhead box O1 (FoxO1) is a member of the FoxO transcription factor family that plays important roles in regulation of glucose homeostasis, cellular proliferation, differentiation, and vascular homeostasis in response to insulin and other growth factors (1-3). Mice lacking FoxO1 die in utero from improper vascular development (4). Overexpression of FoxO1 in primary endothelial cells impairs cell migration and tube formation, whereas knockdown of FoxO1 using siRNA enhances angiogenic function (5). Moreover, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 31 publications
6
39
0
3
Order By: Relevance
“…Because PKA can also directly phosphorylate FoxO1 in endothelial cells, 36 we asked whether this might explain the previously reported apoA-I-mediated increase in insulin synthesis in MIN6 cells 10 and in Ins-1E cells in the present study. The result in Figure 4 showing that apoA-I excludes FoxO1 from the nucleus of Ins-1E cells is consistent with this notion.…”
Section: Discussionmentioning
confidence: 83%
“…Because PKA can also directly phosphorylate FoxO1 in endothelial cells, 36 we asked whether this might explain the previously reported apoA-I-mediated increase in insulin synthesis in MIN6 cells 10 and in Ins-1E cells in the present study. The result in Figure 4 showing that apoA-I excludes FoxO1 from the nucleus of Ins-1E cells is consistent with this notion.…”
Section: Discussionmentioning
confidence: 83%
“…We (38) and others (32) have shown that Icam and Vcam are FoxO1 targets. In primary endothelial cells derived from Foxo1 KR/KR mice, we observed increased expression of Icam1 and decreased expression of Vcam1, consistent with our previous observations that the effects of the FoxO1 deacetylated mutant are target genespecific (15) (Fig.…”
Section: Lower Plasma Tg Levels In Chow-fed Foxo1mentioning
confidence: 79%
“…There is interplay between the PI3K/Akt/FoxO and cAMP/PKA signaling pathways (Chen et al, 2007). FoxO1 is a direct substrate for PKA and PKA phosphorylates FoxO1 at Thr24, Ser256, and Ser319, three known Akt phosphorylation sites (Lee et al, 2011). Epac is an exchange protein activated by cAMP.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%